กลุ่มประชากรและปัจจัยแวดล้อมที่มีผลต่อกลุ่มประชากรไนไตรต์ออกซิไดซิงแบคทีเรียในบ่อเพาะเลี้ยงกุ้ง - ปพิชญา ศรีเทพ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The major concern for culturing shrimp is the controlling of quality of water in the pond and effluent. In general, this can be achieved by biological nitrogen removal via nitrification and denitrification processes. Among these sequential processes, nitrite oxidation by NOB is believed to be the rate-limiting step due to their slow growth rate and more sensitivity to several environmental factors such as salinity and pH than AOB. This study contains 2 parts, first, an investigation of future NOB community in shrimp culture pond in Thailand in order to develop the high strength marine NOB and the other part, study of effects from each type of nitrogen compounds on biofilters nitrite removal rate. In the first part, analyze NOB communities, sediment/water/biofilm were taken to the type of shrimp ponds including outdoor-earthen pond, outdoor-lining pond, indoor pond with water recirculation system and water recirculation system of marine aquarium. The communities of NOB are analyzed by using specific Polymerase Chain Reaction (PCR) amplification, cloning, and sequencing. In this study, primers were selected specifically by ARB program package in order to obtain primers that covered the largest NOB. In this part of the experiment, Nitrospira was found in every culture system. This was due to the fact that every shrimp culture system had nitrite concentration in a range of 0.02-0.17 mg-N/l. The bacteria in this genus could grow in a low range of nitrite (4.9 mg-N/l) because of their K-strategists characteristics and 2 sublineages distribution, which were SublineageII (Nitrospira moscoviensis lineage) and SublineageIV (Nitrospira marina lineage). Furthermore, Nitrobacter was not found in any culture system, because these bacteria had R-strategists characteristics, which means that they could grow well under aerobic and high nitrite condition. It can be seen that if NOB were to be used for treating wastewater from shrimp culture system, then Nitrospira marina should be further developed. Since the said NOB were detected in every culture system, including outdoor earthen pond and indoor culture system, both high and low salinity ponds as well as high and low density shrimp systems.The second part was a study of effects from each type of nitrogen compounds on biofilters nitrite removal rate. These biofilters had passed through immobilization process from indoor shrimp culture system. From studying NOB population on biofilters, it was found that type of nitrogen compounds had no effect on nitrite removal rate at nitrite concentration of 10 mg-N/l. Or in other word, in regardless of the type of nitrogen compounds presented, nitrite removal rates were similar and had minor effects on the change of NOB between biofilters that were immobilized under different nitrogen compound conditions (ammonia, nitrite, and ammonia+nitrite) and biofilters that passed through nitrite removal rate measurement by using immobilized filters. Most of the experiment sets had NOB with 2 sublineages distribution, including SublineageII (Nitrospira moscoviensis lineage) and SublineageIV (Nitrospira marina lineage). From both part of experiment, it can be seen that if NOB were to be used for treating wastewater from shrimp culture system, then Nitrospira marina should be further developed. Since the said NOB were detected in every culture system, including outdoor earthen pond and indoor culture system, both high and low salinity ponds as well as high and low density shrimp systems. In addition, any nitrogen compounds could be used for seed culture development, however, the nitrogen concentration must be low in order to obtain the same kind of bacteria found in shrimp culture system.